Design of magnetic molecularly imprinted polymer nanoparticles for controlled release of doxorubicin under an alternative magnetic field in athermal conditions. Issue 45 (30th October 2015) - Griffete, N.; Fresnais, J.; Espinosa, A.; Wilhelm, C.; Bée, A.; Ménager, C.
Abstract : An innovative magnetic delivery nanomaterial for triggered cancer therapy showing active control over drug release by using an alternative magnetic field is proposed. Abstract : An innovative magnetic delivery nanomaterial for triggered cancer therapy showing active control over drug release by using an alternative magnetic field is proposed. In vitro and In vivo release of doxorubicin (DOX) were investigated and showed a massive DOX release under an alternative magnetic field without temperature elevation of the medium.